Solution-derived YBa2Cu3O7−δ (YBCO) superconducting films with BaZrO3 (BZO) nanodots based on reverse micelle stabilized nanoparticles. Issue 16 (17th March 2015) - Bretos, Iñigo; Schneller, Theodor; Falter, Martina; Bäcker, Michael; Hollmann, Eugen; Wördenweber, Roger; Molina-Luna, Leopoldo; Van Tendeloo, Gustaaf; Eibl, Oliver
Abstract : Hybrid solutions of triflouroacetate YBCO precursors and BZO nanoparticles were synthesized and deposited to yield superconducting YBCO–BZO nanocomposite films. Abstract : Superconducting YBa2 Cu3 O7− δ (YBCO) films with artificial BaZrO3 (BZO) nanodots were prepared using a chemical solution deposition method involving hybrid solutions composed of trifluoroacetate-based YBCO precursors and reverse micelle stabilized BZO nanoparticle dispersions. Microemulsion-mediated synthesis was used to obtain nano-sized (∼12 nm) and mono-dispersed BZO nanoparticles that preserve their features once introduced into the YBCO solution, as revealed by dynamic light scattering. Phase pure, epitaxial YBCO films with randomly oriented BZO nanodots distributed over their whole microstructure were grown from the hybrid solutions on (100) LaAlO3 substrates. The morphology of the YBCO–BZO nanocomposite films was strongly influenced by the amount of nanoparticles incorporated into the system, with contents ranging from 5 to 40 mol%. Scanning electron microscopy showed a high density of isolated second-phase defects consisting of BZO nanodots in the nanocomposite film with 10 mol% of BZO. Furthermore, a direct observation and quantitative analysis of lattice defects in the form of interfacial edge dislocations directly induced by the BZO nanodots was evidenced by transmission electron microscopy. The superconducting properties (77 K) of the YBCO films improved considerably by the presence of such nanodots, which seem to enhance the morphology of the sample and therefore the intergranular critical properties. The incorporation of preformed second-phase defects (here, BZO) during the growth of the superconducting phase is the main innovation of this novel approach for the all-solution based low-cost fabrication of long-length coated conductors.